Effectiveness and cost-effectiveness of proactive and multidisciplinary integrated care for older people with complex problems in general practice: an individual participant data meta-analysis. (22nd June 2018) - Blom, J W; Van den Hout, W B; Den Elzen, W P J; Drewes, Y M; Bleijenberg, N; Fabbricotti, I N; Jansen, A P D; Kempen, G I J M; Koopmans, R; Looman, W M; Melis, R J F; Metzelthin, S F; et al.
Abstract: Purpose: to support older people with several healthcare needs in sustaining adequate functioning and independence, more proactive approaches are needed. This purpose of this study is to summarise the (cost-) effectiveness of proactive, multidisciplinary, integrated care programmes for older people in Dutch primary care. Methods design: individual patient data (IPD) meta-analysis of eight clinically controlled trials. Setting: primary care sector. Interventions: combination of (i) identification of older people with complex problems by means of screening, followed by (ii) a multidisciplinary integrated care programme for those identified. Main outcome: activities of daily living, i.e. a change on modified Katz-15 scale between baseline and 1-year follow-up. Secondary outcomes: quality of life (visual analogue scale 0–10), psychological (mental well-being scale Short Form Health Survey (SF)-36) and social well-being (single item, SF-36), quality-adjusted life years (Euroqol-5dimensions-3level (EQ-5D-3L)), healthcare utilisation and cost-effectiveness. Analysis: intention-to-treat analysis, two-stage IPD and subgroup analysis based on patient and intervention characteristics. Results: included were 8, 678 participants: median age of 80.5 (interquartile range 75.3; 85.7) years; 5, 496 (63.3%) women. On the modified Katz-15 scale, the pooled difference in change between the intervention and control group was −0.01 (95% confidence interval −0.10 to 0.08). No significant differences were found in the other patient outcomes or subgroup analyses. Compared to usual care, the probability of the intervention group to be cost-effective was less than 5%. Conclusion: compared to usual care at 1-year follow-up, strategies for identification of frail older people in primary care combined with a proactive integrated care intervention are probably not (cost-) effective.